Алгоритм формування обводу на основі області розташування еволюти монотонної кривої - Гавриленко, Євген Андрійович; Мацулевич, Олександр Євгенович; Havrilenko, Yevhen; Matsulevych, Oleksandr (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: Алгоритми геометричного моделювання кривих ліній із заданим поєднанням характеристик, що інтерполюють точкові ряди складної конфігурації, є основою розробки систем автоматизованого проектування виробів, обмежених функціональними поверхнями. Необхідні властивості поверхні забезпечуються характеристиками інтерполюючої кривої, яка використовується в якості елементу каркасу моделі, основними з яких є регулярна зміна значень кривини та мінімальна кількість особливих точок. У статті запропоновано спосіб формування послідовності, що складається із скільки завгодно великої кількості заданих вихідних і призначених проміжних точок, які можна інтерполювати монотонною кривою лінією. Спосіб є необхідним етапом створення алгоритму формування обводу, який із заданою точністю представляє криву лінію із заданими властивостями, що інтерпролює послідовність точок довільної конфігурації.Коректність запропонованих у роботі рішень підтверджує розв’язання тестового прикладу. /// EN: Algorithms for geometric modeling of curved lines with a given combination of characteristics interpolating point sequences of complex configurations form the basis for developing computer-aided design systems for products bounded by functional surfaces. The surface is modeled using ruled frameworks, the elements of which are formed by interpolating point sequences. The key characteristics of the interpolating curve, which ensure the required surface properties, are regular changes in curvature values and a minimal number of singular points. This article develops a method for generating a sequence consisting of an arbitrarily large number of specified initial and assigned intermediate points, which can be interpolated by a monotonic curve. The positions of the intermediate points are determined based on pre-assigned characteristics of the interpolating curve—the positions of normals and curvature values. All monotonic curves interpolating the generated point sequence and having assigned characteristics lie within the range of possible intermediate point locations in each section. The length of the specified ranges can be used to estimate the absolute error with which the resulting point sequence defines the interpolating curve. The method developed in this paper is a necessary step in creating a contour generation algorithm located within the boundaries of the possible location of a monotonic curved line. The results obtained in this paper complement those of previous studies. As a result, a contour generation algorithm has been proposed that, with a given accuracy, represents a regular curved line containing a minimum number of singular points and an interpolating sequence of points of arbitrary configuration. The correctness of the solutions proposed in this paper is confirmed by the solution to a test example.
Algorithm for forming a contour based on the location area of the evolute of a monotone curve
Keywords: інтерполяція; монотонна крива лінія; проміжні точки; нормаль; центр кривини; еволюта; область розташування кривої; обвід; похибка; interpolation; monotonous curved line; intermediate points; normal; center of curvature; evolute; curve extension area; outline; distortion